The Role of Parkland for Conservation of Useful Plant Species Diversity in Arba Minch, Southern Ethiopia - Kebebew, Mulugeta (International Journal of Bio-resource and Stress Management, 2019)
This study was conducted in parkland of Arba Minch paradise lodge, Southern Ethiopia from February 2018 to May 2018 with the aim of documenting the plant species diversity; identify major use categories and major factors affecting the parkland of paradise lodge plant composition. Techniques used were focus group discussion, semi-structured interviews, lodge tour and free listing. A total of 124 useful plant species were documented, of which 68 (39.08%) were ornamental plants, 49 (28.16%) food plants, and 24 (13.79%) firewood plants. Fabaceae was the dominant family represented by 10 species, followed by Euphorbiaceae with 8 species each. Parkland of Paradise lodge host a number of endemic and threatened plants in Ethiopia. Species such as Aloe gilbertii, Aloe otallensis, Enset ventricosum were the endemic plant species and Cordia africana, Juniperus procera, Podocarpus falcatus and Olea europea were indigenous plants species which highly treated in the forest. The study indicates that parkland of paradise lodge are contributing to conservation of useful plant species through production of ornamental, food plants, fodder, medicinal, timber and construction. Knowledge gap in plant breeding, lack of planting materials and seeds, lack of agricultural support system, destruction by animals, disease infestation and lack of access to land were among the main factors that affect parkland of paradise lodge plant species diversity. The study recommended that the management of useful plant species in parkland of paradise lodge will be scaled up and further expanded and assisted by agricultural extensions.